1990
DOI: 10.1002/bjs.1800770737
|View full text |Cite
|
Sign up to set email alerts
|

The role of interventional radiology for complications of cholecystectomy

Abstract: This report summarizes diagnostic and therapeutic radiologic procedures inThe operation generally is well tolerated, particularly in young and middle-aged patients. Morbidity is reported to be from 4% to 32% in several large surgical series,'. 3-8 whereas mortality rates vary from 0.4% to 2.5%.1-6, The most frequent complications of chole- 11/56/18794cystectomy are wound infection, abscess formation, ductal injury or ligation, and bleeding.3, "-") Elderly patients undergoing emergency cholecystectomy are more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Recently, some attention has been directed toward the possibility that these nonoperative techniques might be used as definitive treatment for benign bile duct strictures.2'3 Interestingly, the reports on each of these proposed alternatives to operative management often have compared their success rates to antiquated surgical reports in which successes have been modest and outcomes poor. 3 The pertinence of this issue recently has increased because of the rash ofbile duct injuries, which has accompanied the use of laparoscopic cholecystectomy.7-" The present study documents the high success rate ofoperative repair of benign bile duct strictures by evaluation of long-term results. A number of authors have reported series with relatively short follow-up in which the safety ofoperative repair has been documented.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, some attention has been directed toward the possibility that these nonoperative techniques might be used as definitive treatment for benign bile duct strictures.2'3 Interestingly, the reports on each of these proposed alternatives to operative management often have compared their success rates to antiquated surgical reports in which successes have been modest and outcomes poor. 3 The pertinence of this issue recently has increased because of the rash ofbile duct injuries, which has accompanied the use of laparoscopic cholecystectomy.7-" The present study documents the high success rate ofoperative repair of benign bile duct strictures by evaluation of long-term results. A number of authors have reported series with relatively short follow-up in which the safety ofoperative repair has been documented.…”
Section: Discussionmentioning
confidence: 73%
“…They are normally independent of lymphocele volume and they may include abdominal or pelvic mass or pain, hydronephrosis, transplant dysfunction, ipsilateral leg or genital edema, bladder outlet obstruction, and deep vein thrombosis [1,2,9,20,26,33,43]. Ultrasound is known to be the most sensitive method of detecting any kind of intraabdominal¯uid collections including lymphoceles.…”
Section: Discussionmentioning
confidence: 99%
“…For the conservative treatment of posttransplant lymphoceles percutaneous needle aspiration, continuous drainage over a de®ned period of time via various kinds of catheters, and sclerotherapy with several agents have been proposed [2, 4, 10, 12, 14, 22, 24, 26, 33, 34, 37, 39, 40, 42±46]. Operative strategies include a peritoneal fenestration through a laparotomy, minilaparotomy, or via a laparoscopic approach [1±5, 13,23,26,27,30,33,34,43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography and CT are highly sensitive procedures for the detection of postoperative fluid collections. Unfortunately, these modalities produce nonspecific information, and the high frequency (53%) of "benign" or nonsignificant fluid accumulations seem to justify an expectant observation [2,3], On the other hand, delay in diagnosis of a bile collection, hematoma, or abscess may lead to more serious and life-threatening complications [9]. In our series, diagnostic percutaneous aspiration was used expediently upon the initial presentation of postoperative symptoms.…”
Section: Discussionmentioning
confidence: 96%